2017
DOI: 10.3892/mmr.2017.7179
|View full text |Cite
|
Sign up to set email alerts
|

Classical VEGF, Notch and Ang signalling in cancer angiogenesis, alternative approaches and future directions

Abstract: Angiogenesis is the formation of new vessels starting from pre-existing vasculature. Tumour environment is characterized by ‘aberrant angiogenesis’, whose main features are tortuous and permeable blood vessels, heterogeneous both in their structure and in efficiency of perfusion and very different from normal vessels. Therapeutic strategies targeting the three pathways chiefly involved in tumour angiogenesis, VEGF, Notch and Ang signalling, have been identified to block the vascular supply to the tumour. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 124 publications
(116 reference statements)
1
52
0
3
Order By: Relevance
“…Our results reinforce TRPV4 as a negative regulator of angiogenesis, most likely by controlling VEGFR2 localization/ activation, indicating that angiogenesis is regulated by a tight co-ordination between mechanical and soluble (growth factor) signaling. In contrast to the current strategy of inhibiting angiogenesis by targeting VEGF and its receptors (1,(3)(4)(5), our study proposes that TRPV4 is an alternate VEGF-independent strategy to target pathologic angiogenic disorders, such as cancer and retinopathy, which are usually characterized by enhanced VEGFR2 expression/activity. Importantly, targeting a negative regulator of angiogenesis, such as TRPV4, could also offer a potential therapeutic mechanism to enhance angiogenesis in conditions such as ischemic heart disease to improve revascularization.…”
Section: Discussionmentioning
confidence: 80%
“…Our results reinforce TRPV4 as a negative regulator of angiogenesis, most likely by controlling VEGFR2 localization/ activation, indicating that angiogenesis is regulated by a tight co-ordination between mechanical and soluble (growth factor) signaling. In contrast to the current strategy of inhibiting angiogenesis by targeting VEGF and its receptors (1,(3)(4)(5), our study proposes that TRPV4 is an alternate VEGF-independent strategy to target pathologic angiogenic disorders, such as cancer and retinopathy, which are usually characterized by enhanced VEGFR2 expression/activity. Importantly, targeting a negative regulator of angiogenesis, such as TRPV4, could also offer a potential therapeutic mechanism to enhance angiogenesis in conditions such as ischemic heart disease to improve revascularization.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, the migration and immune function of mDCs were inhibited by Y27632 and P‐COF1 BP, which could be due to the reduced actin polymerization and disappearance of dendrites . Vascular endothelial growth factor signaling is also transduced by way of several other intracellular signaling pathways, including Erk, p38MAPK, or the serine/threonine protein kinase Akt, leading to increased cell proliferation, survival, permeability, and migration of endothelial cells . It was reported that VEGF can enhance the phosphorylation of Erk1/2, but not those of p38MAPK or Akt in mDCs .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the central nervous system (CNS) neural-derived signals stimulate the formation of a high density vascular plexus and development of a blood-brain barrier (BBB) (R Daneman et al, 2009; Haigh et al, 2003; Stenman et al, 2008). Many of the key factors that orchestrate embryonic vascular development such as vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), Wnt-β-catenin and Notch, have been identified and their elucidation has facilitated therapies for several diseases, most notably anti-tumor angiogenesis therapies (reviewed in (Adams & Alitalo, 2007; Caporarello et al, 2017; Giacomini et al, 2016; Reis & Liebner, 2013). …”
Section: Introductionmentioning
confidence: 99%